GPi‐DBS for KMT2B‐Associated Dystonia: Systematic Review and Meta‐Analysis. Issue 1 (4th December 2021) - Rajan, Roopa; Garg, Kanwaljeet; Saini, Arti; Radhakrishnan, Divya M.; Carecchio, Miryam; BK, Binukumar; Singh, Manmohan; Srivastava, Achal K.
ABSTRACT: Background: Early evidence suggests good response to pallidal deep brain stimulation (DBS) in DYT‐ KMT2B . Objectives: We aimed to conduct a systematic review and meta‐analysis to assess outcomes and identify predictors of good outcome following GPi‐DBS in DYT‐ KMT2B . Methods: We searched MEDLINE, Cochrane and MDS‐abstracts databases using the MeSH terms " KMT2B and DYT28". We included studies that reported objective outcomes following GPi‐DBS in DYT‐ KMT2B . The BFMDRS‐M (Burke‐Fahn‐Marsden Dystonia Rating Scale‐ Movement) total scores pre‐ and post‐surgery were used to quantify outcomes. We calculated pooled effects using a random effects meta‐analysis and used meta‐regression to identify potential effect modifiers. Multiple linear regression using individual patient data was used to identify predictors of good outcome (>50% improvement from baseline on BFMDRS‐M). Results: Initial searches screened 132 abstracts of which 34 full‐text articles were identified to be of potential interest. Ten studies reporting 42 individual patients, met the inclusion/exclusion criteria and were included in the final review. The mean age at onset was 6.4 ± 5.7 years and 40% were male. The median follow‐up was 12 months (range: 1–264 months). GPi‐DBS resulted in median BFMDRS‐M improvement of 42.7% (range: −103.5% to 95.9%) postoperatively. Pooled proportion of patients experiencing clinical improvement >50% on BFMDRS‐M was 41% (95% CI: 27%–57%). Male gender [β: 22.6, 95% CI: 8.0–37.3, P = 0.004), and higher pre‐operative BFMDRS‐M score [β: 0.62, 95% CI: 0.36–0.87, P < 0.001) were independently associated with better outcome. Conclusion: KMT2B ‐associated dystonia responds effectively to pallidal stimulation. The outcome is better in males and those with more severe dystonia at baseline.